PENERAPAN METODE JARIMATIKA UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SDN 102 PEKANBARU - Firmansyah, Dani; Syahrilfuddin, Syahrilfuddin; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research was the low students learning outcomes class III SDN 102 Pekanbaru. That showed from the daily test results is below of specified KKM. . It is necessary for research to improvements in the learning process through the implementation of jaritmatika method. Jaritmatika method is fingers and aritmatika. This is a method calculate by using students fingers. This method was discovered by Septi Peni Wulandani. In this method, before students using their fingers to calculate numbers, their must understand about how to use fingers. The study design using the PTK (classroom action research) that the implementation is done two cycles, each cycle there are two meetings with the daily test. The subjects were students of class III SDN 102 Pekanbaru totaling 21 peoples. After implementation of jaritmatika method,the teacher activity was increased. Activity percentage of teachers in the first cycle was 70,00% increase in cycle II to 75,00%. Then, the activity of the teacher, student activities also increased. In the second cycle the percentage of student activity is 85%, then increased to 95% in the second cycle. The results showed that the learning outcomes of students increased from prior courses of action in the second daily test into 21,57. Based on these results, it can be concluded that the implementation of jaritmatika method can improve learning outcomes mathematics class SDN 102 Pekanbaru.Keywords : Jaritmatika Method, Learning Outcome Mathematics